Simulation and Experimental Results of a 3 kWp Rooftop PV System in Surabaya - Fitri Dwi Kartikasari; Elieser Tarigan; Alejandro Comte Torres (Politeknik Sukabumi, 2019)
Simulation studies for a PV system would be useful for planning before real implementation, and to predict the cost for a large scale PV system. This work is to simulate a 3 kWp rooftop photovoltaic (PV) system under the climate of Surabaya, Indonesia. SolarGIS PV Planner and RETScreen simulation tools are used in this work. The simulation results are then compared with a full year of measurement results. The results of simulations show that a 3 kWp rooftop system could produce electricity of 4,200 kWh per year, while in the real measurement energy production is found about 3,898 kWh per year. There were slightly different results values of energy output between Simulation and real measurement of the PV system, however statistically it still can be accepted. Economic analysis shows that, under current conditions, a grid-connected PV system investment would give about 5 years of the payback period. Environmentally, the 3 kWp PV system would provide a reduction of CO2 emission of about 2.7 tons per year.